TikTok Trends for English Speaking Learning in Senior High School: Challenges and Limitations - Meinawati, Euis; Calista, Putri; Arfani, Sri (International Journal of Education, Management, and Technology, 2025)
This study investigates students’ perceptions of learning to speak English through TikTok, focusing on its advantages, disadvantages, and challenges as a digital learning medium. The research was conducted at State Senior High School 14 Depok, where 90% of students actively use TikTok for social interaction, study, and other purposes. Using a qualitative descriptive design, data were collected from 50 10th- and 11th-grade students through questionnaires, documentation, and observation. Data were analyzed systematically through stages of collection, reduction, presentation, verification, interpretation, and conclusion to identify themes, patterns, and relationships. Findings indicate that TikTok offers notable benefits for speaking practice, such as accessibility, creativity, and engagement, but also presents limitations, including distractions, superficial content, and uneven quality of language input. Despite these challenges, TikTok retains strong potential as a supplementary tool in English language teaching. The study underscores the importance of enhancing teacher competencies to integrate digital platforms effectively and adapting to technological trends in education. It also suggests extending future research to other English skills, involving a broader range of schools, including vocational institutions, to account for different student profiles.